2012
DOI: 10.1186/1556-276x-7-305
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of SrCO3 nanostructures in methanol/water solution without additives

Abstract: Highly dispersive strontium carbonate (SrCO3) nanostructures with uniform dumbbell, ellipsoid, and rod-like morphologies were synthesized in methanol solution without any additives. These SrCO3 were characterized by X-ray diffraction, field emission scanning electron microscopy, and N2 adsorption-desorption. The results showed that the reaction temperature and the methanol/water ratio had important effects on the morphologies of SrCO3 particles. The dumbbell-like SrCO3 exhibited a Broader-Emmett-Teller surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The SEM image (Fig. 5) showed that the shapes of prepared strontium carbonate particles were rod-like, as also found for the strontium carbonates synthesized in the literature studies (Li et al, 2012;Zhang et al, 2017). It could also be seen from Fig.…”
Section: Resultssupporting
confidence: 79%
“…The SEM image (Fig. 5) showed that the shapes of prepared strontium carbonate particles were rod-like, as also found for the strontium carbonates synthesized in the literature studies (Li et al, 2012;Zhang et al, 2017). It could also be seen from Fig.…”
Section: Resultssupporting
confidence: 79%
“…In the search to find a cheap and straight route to obtain the SrCO 3 phase, it was chose to dry Sr(OH) 2 at ambient atmosphere to take advantage of the reaction with CO 2 present in the air [ 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account some reports about SrCO 3 -Sr(OH) 2 composite as background [ 42 , 43 , 44 , 45 , 46 , 47 ], and due the SrCO 3 -Sr(OH) 2 /PPy nanocomposite has not been studied as a photocatalyst candidate, this manuscript describes a modified strategy for the preparation of SrCO 3 -Sr(OH) 2 nanocomposite, followed by coating with the semiconducting polypyrrole (PPy) to increase its photoactivity in the visible light range. Both SrCO 3 -Sr(OH) 2 and SrCO 3 -Sr(OH) 2 /PPy nanocomposites were tested for photodegradation of MB dye under visible light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Alternatively, alkaline earth metallic strontium (Sr) based materials such as Sr(OH) 2 , SrS, SrPO 4 and SrCO 3 have given much attention due to their excellent electrical conductivity, low cost and ease to prepare. [20][21][22][23] Mahmood-Ul-Hassan et al have prepared graphene oxide (GO) based SrS nanorods to exhibit excellent specific capacitance of 1831.14 F/g at 3 mA/cm 2 current density. The presence of GO thin film has enhanced the electrochemical surface area and provides better electrical conductivity to charge storage property.…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous electrode materials reported till date, the transition metal oxide/hydroxide like MnO 2 , NiO 2 , RuO 2 , SnO 2 , Co 3 O 4 , Ni(OH) 2 , Co(OH) 2 etc are mainly offering reversible redox property due to the tunable electrochemical reaction [16–19] . Alternatively, alkaline earth metallic strontium (Sr) based materials such as Sr(OH) 2 , SrS, SrPO 4 and SrCO 3 have given much attention due to their excellent electrical conductivity, low cost and ease to prepare [20–23] . Mahmood‐Ul‐Hassan et al .…”
Section: Introductionmentioning
confidence: 99%